The 12-month prevalence and nature of adverse experiences resulting in emergency medical presentations associated with the use of synthetic cannabinoid products - Winstock, A.; Barratt, Monica (John Wiley & Sons, 2013)
Objective: A wide range of synthetic cannabinoid products have recently become available through the Internet and shop fronts across the globe. Concerns about the consequences of their use have been prompted by increasing reports of emergency department presentations. Methods: An anonymous global online survey was conducted using a research tool based on previous work carried out by the group. Data collection took place during a 4-week period at the end of 2011. Results: Among 950 last-year users, 23 (2.4%) reported having sought emergency medical treatment following the use of a synthetic cannabinoid product. The most common presentations were panic and anxiety, followed by paranoia and breathing difficulties. Recent users who reported seeking emergency medical treatment were significantly younger (median age 20 years, interquartile range 18–22) than those who did not report seeking treatment (median age 23 years, interquartile range 19–28; Mann–Whitney test, z = 2.89, p = 0.004). Conclusions: Synthetic cannabinoid use appears to be associated with a high prevalence of adverse experiences among users, especially younger users. Further research is required to determine whether particular compounds carry a higher risk of harm than others and to assess potential consequences of longer term use.